2004
DOI: 10.1292/jvms.66.911
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemic of Caprine Arthritis Encephalitis in Japan: Isolation of the Virus

Abstract: ABSTRACT. A disease characterized by arthritis of carpal joints and occasionally by pneumonia was seen among goats on a farm in Nagano prefecture of Japan in the summer of 2002. Serological investigation was done on 30 goats, that is one group on the farm by agar gel immunodiffusion tests using maedi-visna virus as the antigen, and 19 goats were positive. The caprine arthritis encephalitis vi rus genome was detected in peripheral blood leukocytes from several antibody-positive goats. Two goats among them were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…High magnification of virions (C) showed the ultrastructure of the smooth antigenic external surface of virions, and budding-like virions with stalklike structure from the surface of the syncytium were examined (D) (arrow; bar = 100 nm., 40,000× magnification). (6,15,23,24). Therefore, it was again confirmed that our primary goat synovial cells and cultivating system were appropriate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High magnification of virions (C) showed the ultrastructure of the smooth antigenic external surface of virions, and budding-like virions with stalklike structure from the surface of the syncytium were examined (D) (arrow; bar = 100 nm., 40,000× magnification). (6,15,23,24). Therefore, it was again confirmed that our primary goat synovial cells and cultivating system were appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…The suspension was centrifuged at 2000 rpm at 5 °C for 20 min. The mononuclear cells were separated as an obvious thin white layer above the red 6 cell/mL of isolated mononuclear cells per flask were resuspended in the medium for their differentiation to macrophages at 37 °C and 5% CO 2 for 7 days. The medium contained RPMI 1640 supplemented with L-glutamine (2 mM), gentamicin (50 µg/ml.…”
Section: Mononuclear Cell (Monocyte) Isolation and Cultivationmentioning
confidence: 99%
“…Live animal trading across national boundaries is considered an important cause of horizontal CAEV transmission, whilst ingestion of colostrums and milk represent important causes of transmission from mother to offspring [3,4]. In 2002, CAEV was identified in Japan [10]. Infected goats develop anti-CAEV antibodies and develop a persistent, lifelong infection.…”
mentioning
confidence: 99%
“…At present in Japan, only Caprine Arthritis Encephalitis virus, Scrapie and Visna Maedi have been examined in small ruminant populations, having recently been the subject of epidemiological studies [10,12,13,16,Giangaspero et al,unpublished]. No previous epidemiological surveys on BDV have been undertaken in small ruminants in Japan.…”
mentioning
confidence: 99%